Sampling theory : beyond bandlimited systems - Eldar, Yonina C. (Cambridge : Cambridge University Press, 2014)
Covering the fundamental mathematical underpinnings together with key principles and applications, this book provides a comprehensive guide to the theory and practice of sampling from an engineering perspective. Beginning with traditional ideas such as uniform sampling in shift-invariant spaces and working through to the more recent fields of compressed sensing and sub-Nyquist sampling, the key concepts are addressed in a unified and coherent way. Emphasis is given to applications in signal processing and communications, as well as hardware considerations, throughout. With 200 worked examples and over 200 end-of-chapter problems, this is an ideal course textbook for senior undergraduate and graduate students. It is also an invaluable reference or self-study guide for engineers and students across industry and academia.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Signal processing -- Digital techniques -- Study and teaching (Higher); Signal processing -- Digital techniques -- Study and teaching (Graduate); Signal processing -- Statistical methods -- Study and teaching (Higher); Signal processing -- Statistical methods -- Study and teaching (Graduate); Sampling (Statistics)